Spatial network analysis based on Space Syntax Methodologies. The evolution of integration in the historic cities of Toledo and Alcalá de Henares - Arnáiz, Mayte; Ruiz-Apilánez, Borja; de Ureña, José María (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
This paper shows the decisive influence of urban growth on accessibility (Space Syntax integration) of the pre-existing city and the historical centre in particular. Using Space Syntax theories and tools, this paper focuses in the study of integration of each spatial element (mainly streets) of the cities of Toledo and Alcalá de Henares in four different stages–1950s, 1970s, 1990s and 2010s–and pays special attention to the particular evolution of their historic city. In this respect, such morphological analysis becomes a pioneer attempt to combine both Space Syntax methodologies and a Conzenian approach –as it is evolutionary–. It shows how the accessibility pattern of urban spatial networks evolve through time as city grows, and how this can increase or decrease the accessibility of each particular element.